1995
DOI: 10.1073/pnas.92.5.1495
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of the cDNA for a polypeptide associated with rat hepatic sinusoidal reduced glutathione transport: characteristics and comparison with the canalicular transporter.

Abstract: Using the Xenopus oocyte expression system, we previously identified an -4-kb fraction of mRNA from rat liver that expresses sulfobromophthalein reduced glutathione S-conjugate (BSP-GSH)-insensitive and an -2.5-kb fraction expressing BSP-GSH-sensitive reduced glutathione (GSH) transport. From the former, a 4.05-kb cDNA was cloned and characterized as the putative rat canalicular GSH transporter. Starting with a cDNA library constructed from the -2.5-kb fraction, we have now isolated a single clone that leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
0
23
2
Order By: Relevance
“…RNA was isolated from various cell lines according to the method of Chomczynski and Sacchi (19). RNA (20 g) was separated on a 1% agarose gel with 6.7% formaldehyde, blotted onto a nylon membrane by capillary transfer, then hybridized to a 1.5-kb cDNA derived from a subcloned insert corresponding to nucleotide 1132-2623 of the rat canalicular GSH transporter (RcGshT) and to a full length 2.7-kb cDNA for the rat sinusoidal GSH transporter (RsGshT) as described previously (4,5). The cDNA probes were labeled with 32 P-dCTP by random priming (Primer-It II Kit; Stratagene, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNA was isolated from various cell lines according to the method of Chomczynski and Sacchi (19). RNA (20 g) was separated on a 1% agarose gel with 6.7% formaldehyde, blotted onto a nylon membrane by capillary transfer, then hybridized to a 1.5-kb cDNA derived from a subcloned insert corresponding to nucleotide 1132-2623 of the rat canalicular GSH transporter (RcGshT) and to a full length 2.7-kb cDNA for the rat sinusoidal GSH transporter (RsGshT) as described previously (4,5). The cDNA probes were labeled with 32 P-dCTP by random priming (Primer-It II Kit; Stratagene, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Both transporters exhibit low affinity (high K m ), bidirectional, Na-independent GSH transport, and they show no sequence homology and represent two unique genes. The sinusoidal GSH transporter mRNA was only expressed in liver whereas the canalicular transporter mRNA was found in all organs examined (4,5). The functional distinction between these two transporters relies on the selective cis-inhibitory effect of BSP-GSH on the sinusoidal GSH transporter but not the low affinity canalicular GSH transporter (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(7,11,12) Furthermore, Devi and Devaraj (13) reported that the acrolein-generating cyclophosphamide (36,37) induced both weak and strong GST-P expression in all rat hepatocytes, and indicated that the strongly GST-P + single hepatocytes and minifoci were distributed along the hepatocyte strands. Since acrolein is excreted through the GS-X pump as a GSH conjugate, (38,39) this finding indicated that the induction of GST-P expression is mediated through injury of the transporter by the toxic action of acrolein. Thus, the induction of GST-P expression serves to inactivate acrolein toxicity, resulting in the formation of GST-P + single hepatocytes, as reported previously.…”
Section: Discussionmentioning
confidence: 97%